Digital Image Watermarking (DIW) yang kuat menggunakan SWT dan Watermark berbentuk data melingkar - Yoiceta Vanda; Dwiyanto Dwiyanto; Agus Nugroho (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2025)
Digital images can be easily copied and distributed illegally using widely available software tools. A technique is needed that can be used to copyright protection. This technique can show the identity of the owner, so it can be used to track its authentication, namely the watermarking technique. Watermarking methods that embed side information into images with the aim of protecting copyright have been proposed. So far, these methods have been defeated by simple attacks such as rotation, translation and scaling. In this research, a novel digital image watermarking (DIW) system that takes advantage of the Wavelet Transform properties to embed a spread spectrum circular symmetric watermark in an image is proposed. Watermark is invisible, its mean imperceptible to the human eye but can be detected or extracted by software. Watermark robustness against translation, rotation, scaling, median filter, and adaptif filter attacks is achieved by the proposed method. Successful experiments showing the performance of the method to geometric transformation.